Teacher Talk and Learners’ Learning Styles in Learning English over the Pandemic Era: A Psycholinguistic Study - Nasmilah Nasmilah (Universitas Jambi, Indonesia, 2022)
Teacher Talk (TT) in the classroom is a crucial topic in the research, as evidenced by the fact mentioned earlier. Poor teacher talk might result from a lack of instructor attention. This research observed how teacher talk and student learning style interplayed in the learning English process at SMAN 6 and SMKs Harapan Bangsa Watang Pulu in Sidrap, South Sulawesi Province, Indonesia, during the post-covid 19. This research used a mixed method. The data were from observation and questionnaire surveys of 5 classes in SMAN 6 and SMKs Harapan Bangsa Watang Pulu in Sidrap. The result of the psycholinguistic analysis categorized the learning style of the observed learners as high interpretation as a dominant style. The results also showed a significant interplay level between TT and learning style and auditory learning is the most dominant. The researcher found that from the six types of learning styles, visual, auditory, kinesthetic, and tactile in the learning process in the post-pandemic era, individual and group learning styles were never conducted in the class activities during the teaching-learning process post-pandemic. The research implication is teacher talk is an indispensable part of foreign language teaching in organizing activities, and the way the teacher talk (TT) not only determines how well they transfer the lessons. At the same time, it also has a good understanding of the learners’ learning styles.